Subcultural distinction in East Asian education: the case of high school rock in Taiwan - Wang, Chi-Chung (The University of Edinburgh, 2017)
What kind of rock culture would grow out of an exam-oriented educational system? In the western rock world, self-learning has been characterized as most popular musicians’ principal learning pattern, closely intertwined with the “DIY” ethos and the counter school culture. This research aims to present a different case, that of the “schooled” rock music in Taiwan. Over the last three decades, rock music in Taiwan has grown in popularity, while Taipei has gradually earned the reputation of being the “Mandarin pop/indie capital.” In its developmental process, a few characteristics are worthy of the attention of both the Sociology of Education and youth cultural studies. Firstly, learning rock instruments in regular high school is the main route for teenagers to gain access to rock culture. Secondly, where elite students tend to devote more time to rock music activities than other students, their musical repertoire is characterized by producing covers of heavy metal tunes instead of song-writing. This thesis will probe the rationale behind this phenomenon by answering the following questions: What can best explain the appeal of heavy rock to Taiwanese elite high school students? Why do they not write their own songs? Drawing upon data collected through a school ethnography, it is revealed that the ways Taiwanese elite high school students participate in musical activities can be best understood to be part of a subcultural milieu marked by the collective pursuit of “dual excellence in both study and play”. In this symbolic space, the demanding technical requirements for acquiring several playing techniques allow rock to become a rankable sphere of activity in which elite students struggle for subcultural superiority according to measurable musical standards. The emphasis on instrumental virtuosity conforms to students’ competitive disposition manufactured through academic exams. With these features, rock music becomes a particular form of subcultural activity which allows elite students to not only resist educational control, but also exert symbolic violence over peers of lower-ranked high schools by showing technical superiority. This thesis extends the CCCS’s subcultural solution to the analysis of “subcultural distinction”. In distinction to the “internal perspective” of Sarah Thornton’s conception of subcultural capital (1995), a more holistic framework is developed to explore the relationship between the wider patterns of social division, young people’s subcultural participation, and the shaping of the value hierarchy both within and outside the subcultural sphere. Further, the thesis explores the educational system’s active role in shaping youth subcultures. I demonstrate how education in Taiwan is institutionally mediated by the exam regime to be a powerful logic of social differentiation, and the ways young people’s subcultural choices are constrained by their educational career advance from high school to university. The study also has important implications for the educational policy making in Taiwan. By looking at how students “play,” I propose a new exploratory route to illuminate the widespread impact of the exam-oriented educational system on students’ creativity and identity formation.
Keywords: East-Asian education; distinction; symbolic resistance; rock; educational career; leisure career; youth (sub)culture